The Impact and Challenges of Parak Acil Online in Banjarmasin’s E-Government Transformation - Devi Anastaia Budiawaty Teguh; Budi Kristanto (Teknika, 2025)
The rapid development of information and communication technology (ICT) in the Industrial 4.0 era has transformed governance globally, including in Indonesia, where e-government initiatives are a national priority. This study examines the implementation and impact of Parak Acil Online, a digital platform introduced by the Population and Civil Registration Office (Disdukcapil) in Banjarmasin, aimed at streamlining public service delivery for population documents such as e-KTP, family cards, and birth certificates. The research employs a qualitative approach, guided by the E-GovQual and Delone & McLean IS Success models, to evaluate the platform’s performance across six dimensions: Ease of Use, Trust, Functionality of Interaction Environment, Reliability, Content and Appearance, and Citizen Support. Findings reveal that Parak Acil Online significantly enhances service accessibility, transparency, and efficiency. However, challenges persist, including digital literacy gaps, infrastructure limitations, and system performance issues, such as delays and occasional crashes during peak usage. Respondents highlighted the need for improved accessibility features, real-time support tools, and enhanced backend optimization. This study contributes by providing a comprehensive evaluation framework and actionable insights for optimizing e-government platforms in developing regions. By addressing these challenges, Parak Acil Online can achieve sustainable digital transformation and serve as a benchmark for equitable public service delivery in Indonesia and beyond.